Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.bcp.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Expression, regulation, and function of drug transporters in cervicovaginal tissues of a mouse model used for microbicide testing

Abstract: P-glycoprotein (P-gp), breast cancer resistance protein (BCRP), and multidrug resistance protein 4 (MRP4) are three efflux transporters that play key roles in the pharmacokinetics of antiretroviral drugs used in the pre-exposure prophylaxis of HIV sexual transmission. In this study, we investigated the expression, regulation, and function of these transporters in cervicovaginal tissues of a mouse model. Expression and regulation were examined using real-time RT-PCR and immunohistochemical staining, in the mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…The presence of high MRP4 in vaginal epithelium compared to colorectal epithelium at both genetic and protein level may account for the increased accumulation of tenofovir in the colorectal compared to cervicovaginal mucosa . This is consistent with functional studies performed in a mouse model that found that MRP4 inhibitors significantly affected the disposition of tenofovir gel in genital tissues . Similarly, the presence of P‐gp in vaginal mucosa may indicate difficulty in reaching appropriate drug concentration within the female genital tract, as several ARVs being considered for PrEP, including maraviroc, darunavir, raltegravir, and cabotegravir, have been identified substrates of P‐gp .…”
Section: Role Of Drug‐metabolizing Enzymes and Transporters In Femalesupporting
confidence: 71%
See 1 more Smart Citation
“…The presence of high MRP4 in vaginal epithelium compared to colorectal epithelium at both genetic and protein level may account for the increased accumulation of tenofovir in the colorectal compared to cervicovaginal mucosa . This is consistent with functional studies performed in a mouse model that found that MRP4 inhibitors significantly affected the disposition of tenofovir gel in genital tissues . Similarly, the presence of P‐gp in vaginal mucosa may indicate difficulty in reaching appropriate drug concentration within the female genital tract, as several ARVs being considered for PrEP, including maraviroc, darunavir, raltegravir, and cabotegravir, have been identified substrates of P‐gp .…”
Section: Role Of Drug‐metabolizing Enzymes and Transporters In Femalesupporting
confidence: 71%
“…13 This is consistent with functional studies performed in a mouse model that found MRP4 inhibitors significantly affected the disposition of tenofovir gel in genital tissues. 23 Similarly, the presence of P-gp in vaginal mucosa may indicate difficulty in reaching appropriate drug concentration within the FGT as several ARVs being considered for PrEP, including maraviroc, darunavir, raltegravir, and cabotegravir, have been identified substrates of P-gp 15,24 . With the exception of cabotegravir, these drugs appear to penetrate well to the FGT although, exposures are consistently lower than in colorectal tissue 25,26 , consistent with higher P-gp expression observed in vaginal tissue over colorectal tissue at mRNA level.…”
Section: Role Of Drug Metabolizing Enzymes and Transporters (Dmet) Inmentioning
confidence: 99%
“…For example, postmenopausal women have been found to have decreased ABCB1 (P-glycoprotein) expression in the vagina compared to premenopausal women [28]. Differences in drug transporter expression by phase of estrous cycle have been seen in a mouse model [29]. Changes in uptake or efflux drug transporters may have resulted in our findings of decreased DPV concentrations in cervical tissue; however, the drug transporters involved in DPV distribution are not yet known [30,31].…”
Section: Discussionmentioning
confidence: 79%
“…The menstrual cycles of all candidate female mice were synchronized by intraperitoneal administration of pregnant mare serum gonadotrophin (PMSG, 5 IU/20 g) 70 . Three days later, a short stumpy uterus made it easy to establish a murine IUA model by electrocoagulation, which was marked as day 0, as previously described 71 .…”
Section: Murine Iua Model Establishment and Drug Treatmentmentioning
confidence: 99%